Women's perspectives on health facility and system levels factors influencing mode of delivery in Tehran: a qualitative study - Mahboube Shirzad; Elham Shakibazadeh; Ana Pilar Betran; Meghan A. Bohren; Mehrandokht Abedini (BMC, 2019)
Abstract Background Iran has one of the highest national caesarean section rates worldwide. Few studies explored in-depth the health-facility and health-system level factors that affect women's choices on mode of delivery in Iran. The aim of this study was to explore the health-facility and health-system level factors affecting women's preferences on mode of delivery in Tehran. Methods We conducted a qualitative study using in-depth face-to-face interviews with women between October 2017 and May 2018. Study participants were sampled purposively from a range of health service settings to include women of varying experiences regarding childbirth. Eligibility criteria were Persian-speaking, women with or without childbirth experiences. All interviews were audio-recorded and lasted 30-45 min. After verbatim transcription of the interviews, we created a preliminary thematic framework to analyze the data. A combined inductive (themes emerging from the data) and deductive (key concepts across existing frameworks) approach was used during data analysis. Results In total, 26 in-depth interviews were conducted. Five central themes influencing women's preferences on mode of delivery emerged from the analysis: (1) health system conditions (important differences between the quality of care provided at private and public hospitals; staff shortages, skills, competency, motivation and also accessibility to staff during the longer time required for a vaginal delivery; policies and protocols on vaginal birth after cesarean, pain relief for vaginal birth, and having companion during labor; (2) standards of care in facilities (physical condition in facilities; physical examinations and procedures; continuous and organized care; ethics); (3) interaction between women and providers (communicating in a supportive manner with women and communication women's partners/families); (4) preserving women's dignity (delivering high quality and respectful care); (5) provision of information (education about pregnancy and childbirth including environment in facility, labor processes/procedures, and the risks and benefits of both vaginal delivery and caesarean section). Conclusions Our study suggests, there are barriers to increasing demand for and satisfaction with vaginal birth, such as women's perceived sub-optimal quality of care during labor and birth, understaffed facilities that lack standard protocols and have limited physical space, and lack of privacy and dignity. The multifactorial nature of the increase of unnecessary Cesarean section calls for multicomponent interventions to revert this trend. These interventions need to address the health-systems' and health-facilities' deficiencies behind women's preference for Cesarean section.